Шлюбні орієнтири мешканців Вінниці другої половини XVIII ст. (за матеріялами метричних книг) - Зінченко, А. (Краєзнавство, 2023)
Стаття має метою проаналізувати, як у записах метричних книг парохій міста Вінниці другої половини XVIII ст. відобразилися соціяльні та соціокультурні орієнтири парохіян у виборі шлюбних пар та свідків шлюбного обряду. Під шлюбними орієнтирами тут розумітимемо зафіксовані метричних книгах різноманітні варіяції у виборі пари при поєднанні у сімейне подружжя обрядом вінчання. На жаль, у силу історичних соціокультурних обставин більшість руського населення Правобережної України (у тому числі міщан) були позаписьменними, через це не залишили по собі листування, щоденників, а тому їхні міркування та аргументи щодо вибору шлюбної пари практично не відомі. Хіба що зрідка про них можна дізнатися в матеріялах судових проваджень. В такому разі в ході подібного дослідження можна було б говорити навіть про шлюбні стратегії (розгорнутий виклад мотивів вибору шлюбної пари). Але це в силу щойно сказаного є вельми проблематичним. Нині ж автор бачить своїм завданням аналіз шлюбних орієнтирів. Marriage metrics are a specific private law source that formalized the fact of entering into a marriage relationship. The texts of the church registers themselves point to social (including ethno-social) guidelines in choosing a marriage partner: they mostly chose from people of the same social stratum. Noble grooms took noblewomen as their mates, and if one of the brides was a Roman Catholic, Roman Catholics (Poles) were most often chosen as witnesses. If officials or people who served in the Royal Army were involved in the wedding ceremony, or if one of the bride and groom was Polish, the entry in the metric was made in Polish. The invitation of shop foremans, church titers, and influential Ruthenian burghers to witnesses indicates a certain prestige level. There are isolated cases when a representative of the lower social strata (an ordinary burgher or even a subject) married the daughter of an influential Ruthenian burgher. Several records record a special marriage license: in one case, it was a wedding on a pre-Lenten Sunday (the license was given by a Bratslav uniate official), in another case, the bride was of Roman Catholic faith and the marriage license was given by a Latin canon. Church records clearly witness the gravitation of the Vinnytsia clergy to the nobility stratum. This gravitation showed itself in clergy’s striving to identify itself with nobility and to surround itself with persons of noble origin when performing important acts of social partnerships: when selecting godparents for priests’ children and witnesses at their weddings. The above indicates that the records in the marriage metrics of the mentioned parishes, despite their specificity and brevity, reflect the characteristic features of socio-cultural relations in the region.